Erythema ab igne: Usual site, unusual cause - D Manoharan (Wolters Kluwer Medknow Publications, 2015)
Erythema ab igne is reticular erythematous pigmented dermatoses seen in patients exposed to prolonged or repeated sub-threshold Infrared radiation inadequate to cause burns. Here, we report a case of erythema ab igne in a 40-year-old male patient seen over the abdomen due to prolonged laptop use.